Analysis of Catfish Cultivation Business and its Development Prospects in Koto Mesjid Village Kampar District, Riau Province - Hendrik, Hendrik (Jurnal Perikanan dan Kelautan, 2022)
Striped Catfish (Pangasius sp) is a freshwater fish that has good prospects for development because it has important economic value, this is because the selling price is quite high and can be marketed in fresh and processed forms. Striped catfish in Riau Province has been developed by the community, especially in Kampar Regency. This research was conducted in Koto Masjid Village, Kampar Regency in November 2021. This study aims to determine the business feasibility and prospects for the development of striped catfish farming. This research uses survey method. Data analysis was carried out on aquaculture with a pond area of ​​1000 m2. Business analysis is carried out on investment, fixed capital, working capital and profits. Data analysis used to determine the financial feasibility of a business is Revenue Cost of Ratio (RCR), financial Rate of Return (FRR), and Payback Period of Capital (PPC). Respondents in this study were Striped Catfish cultivators, feed entrepreneurs, and hatcheries. The results showed that the catfish farming business was very feasible to be developed both in terms of profit, business feasibility and sustainability aspects. The prospect of developing this business is very good in terms of input, production process, and market demand. In addition, there is still land available for striped catfish cultivation, making it possible for business expansion